The Contribution of Geomagnetic Activity to Polar Ozone Changes in the Upper Atmosphere - Cong Huang; Fuxiang Huang; Xiaoxin Zhang; Dandan Liu; Jingtian Lv (Advances in Meteorology)
Energetic particle precipitation (EPP) has significant impacts on ozone depletion in the polar middle atmosphere during geomagnetic activity. It is well known that solar ultraviolet (UV) radiation plays an important role in ozone generation. Therefore, it is interesting to compare the contributions of EPP and solar UV to ozone changes in the polar upper atmosphere. In this article, we use the annual average Ap index to denote the annual-mean magnitude of the geomagnetic activity, which is closely correlated with the EPP flux, and the annual average F10.7 index to denote the annual-mean magnitude of the solar radiation, which is somewhat related to the solar UV. We adopt the 5° zonal annual-mean ozone profile dataset to study the statistical characters between the ozone dataset and the Ap, F10.7 indices. Multiple regression analysis shows that the contributions of geomagnetic activity are not negligible and are of a similar order of magnitude as the solar UV radiation in the polar upper atmosphere (above 10 hPa). The results also show that high-speed solar-wind-stream-induced and coronal-mass-ejection-driven geomagnetic activity is of the same order of magnitude. There are interhemispheric differences according to our multiple regression analysis. We discuss the possible causes of these differences.